THE INFLUENCE OF THE FRAUD HEPTAGON ON FINANCIAL STATEMENT FRAUD IN ENERGY SECTOR COMPANIES INDONESIA - Alya Melsa Luna; Mohamad Zulman Hakim; Ananta Pasya Octaviani; Elvina Sephia Hardiyanti; Marisa Harahap (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study examines the influence of the Fraud Heptagon elements on financial statement fraud among consumer cyclical companies listed on the Indonesia Stock Exchange (IDX) during the 2021 to 2024 period. The Fraud Heptagon expands the Fraud Triangle and Fraud Diamond theories by adding two behavioral aspects, ignorance and greed, to provide a deeper understanding of the psychological drivers of fraud. Using a quantitative approach with purposive sampling, the study focuses on companies that consistently published complete annual reports and recorded positive profits. The research analyzes factors such as financial stability, financial targets, external pressure, personal financial needs, board changes, monitoring effectiveness, and auditor rotation. The findings show that personal financial needs and ignorance significantly increase the likelihood of financial statement fraud, while other variables have no significant effect. This indicates that individual financial pressure and negligence toward internal control systems are the main factors contributing to fraudulent reporting in Indonesia’s consumer cyclical sector.